Handbook of research on urban informatics : the practice and promise of the real-time city - Foth, Marcus (Hershey, PA : Information Science Reference, 2009)
'This book exposes research accounts which seek to convey an appreciation for local differences, for the empowerment of people and for the human-centred design of urban technology'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cities and towns -- Effect of technological innovations on -- Case studies; Sociology, Urban -- Case studies; Computer networks -- Social aspects; Information technology -- Social aspects; Telecommunication -- Social aspects; Information society